Factors Influencing Poverty Outreach Among Microfinance Institutions in Latin America - Crowther, Naomi (International Finance Corporation, Washington, DC, 2017)
This report investigates the poverty outreach of 14 microfinance institutions (MFI) across six Latin American countries: Peru, Colombia, Bolivia, Ecuador, Guatemala, and Nicaragua. It uses information that these MFIs have collected in terms of poverty likelihood using the Progress Out of Poverty Index (a.k.a. Simple Poverty Scorecard) supplemented by in-depth interviews with industry experts. The following is a summary of the report findings. Those who reach the highest percentage of poorer clients are the ones that focus on clients in regions with higher percentages of poor people. The report also surfaced two interlinked factors driving poverty outreach across some Latin American markets: competition and over-indebtedness. Increased banking saturation is changing the landscape of microfinance, pushing MFIs who do not explicitly target the poor to provide loans to poorer individuals. The wealthier the client of an MFI the larger the average loan size and number of loans that they receive, which is consistent with the MFIs’ financial sustainability. Across countries, MFIs reach the lowest percentages of poorer households in regions with lower population density and challenging geographies. The report also found significant correlations between the number of previous loans and the size of subsequent loans, but non-significant correlations between the percentage of poorer MFI clients in a region and the loan size. The report also triangulates information gleaned from MFI interviews to shed light on their behavior, such as the commercial strategies of these MFIs. Micro-level data was also used to understand the MFIs’ client profiles in terms of loan size and the frequency with which they receive loans.